Aerob and Anaerob Treatments to BOD, COD, pH, and Dominant of Bacteria of Dessicated Coconut Industry Wastewater of PT. Global Coconut, Radey, South Minahasa - Hermanus, Muson B.; Polii, Bobby; Mandey, Lucia C. (Jurnal Ilmu dan Teknologi Pangan, 2015)
Industrial waste dessicated coconut are coconut water, water from coconut meat washing and water from the equipment washing. The aims of this research are to find out the level of organic contaminant (BOD and COD) after aerob and anaerob treatments and to determine the dominant bacteries. The research was done in PT Global Coconut Radey Minahasa on June 2015 and laboratory of FMIPA Unsrat. The research conclude that aerob treatment (with oxygen) are better in decreasing BOD, COD and pH values and are better in decreasing BOD, COD, and pH values and the dominant bacteries are Escherichia coli, Streptococcus sp, Staphylococcus sp, and Clostridium sp compared with anaerob treatment (without oxygen). Keywords : industrial waste, coconut water, contamination of organic materials, aerob treatment, anaerob treatment